Kajian Literatur Dampak Positif Penerapan Konsep Rancangan Biofilia terhadap Kesehatan Mental Manusia dengan Metode Studi Kasus - Rahardjo, Astrid; Rianto Widjaja, Robert (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
The aim of a case study research method is to understand the meaning, the depth as well as the methods performed in previously done researches on any given context and phenomenon. Within the topic of the relationship between the use of biophilic architecture concept and its positive impact towards its users’ mental health, literature research under the same theme is of a necessity in order to gain a stronger base for next researches. This study is conducted using three case studies, each discussing their research backgrounds, the experimental and exploratory methods used, the results in details. Using case study method, this study has succeeded in extracting the finding and the gap of the research as described in form a table.